Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution

Evaluating suitability of confined impinging jet reactor for exothermic reactions: hydrodynamics, residence time distribution, and heat transfer - Khan, Muzammilanwar S.; Mane, Mayur; Kulkarni, Amol A. (AICHE Journal, 2022)
Effect of confinement (wall proximity) of a confined impinging jet reactor (CIJR) on the flow field, residence time distribution and heat transfer are explored, through experiments and CFD simulations. Hydrodynamic characteristics are evaluated for different parameters namely confinement, impinging jet velocity, temperature gradient, and so on. For 2 mm confinement, highest values of dispersion number and overall heat transfer coefficient are observed due to interaction of turbulent eddies followed by the effect of reactor wall proximity. For the CIJR having confinements above 10 mm, jet velocity need to be greater than 3 m/s to achieve both, excellent mixing efficiency and high heat removal rate. Empirical correlations for Dispersion and Nusselt numbers as a function of Re-j and L/D are obtained, over a range of 500 <= Rej <= 3000\$\$ 500\textbackslashle {\textbackslashmathit{\textbackslashoperatornameRe}}_j\text backslashle 3000 \$\$ and 5 <= L/D <= 35\$\$ 5\textbackslashle L/D\textbackslashle 35 \$\$, which correspond to jet velocity of 0.5-3 m/s. The present study gives a basis for designing CIJR suitable for rapid, homogeneous, exothermic reactions.
Keywords: confinement; exothermic reactions; heat transfer; impinging jets; residence time distribution